(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Cerodontha handlirschi Nowakowski collected on Central Alps (Alpi Retiche), new for the Italian fauna is reported. A malformation on antennae of a male is described and illustrated.